Relationship models between egg weight and internal quality of Alabio duck eggs (Anas platyrhynchos Borneo) - Danang Biyatomoko; Lilis Hartati; Febriyanti Febriyanti; Gamaliel Simanungkalit (Politeknik Negeri Jember, 2023)
This research aimed to determine the relationship models and phenotypic correlation between the egg weight of Alabio duck (Anas Platyrhynchos Borneo) and the Haugh unit (HU), albumen weight, yolk weight, albumen index, and yolk index. Five hundred eggs weighing 65.7 ± 4.62 g were collected from a flock of 32-week-old commercial laying hens as objects for this experiment. The observed variables were egg weight, albumen weight, yolk weight, albumen index, and yolk index. The data was analyzed using simple linear regression and Pearson's correlation coefficient (r). A significant correlation (P < 0.05) was found between egg weight and HU, albumen weight, yolk weight, and yolk index., with an r of -0.11, 0.83, 0.70, and 0.19, respectively. However, there was no significant correlation between egg weight and albumen index (P > 0.05). These results indicated that egg weight could be used as a variable to appropriately predict albumen weight and yolk weight with the equations y = -0.11 + 0.56x and y = -2.10 + 0.37x for albumen and yolk weight, respectively. However, egg weight as a single variable could not accurately predict the HU and yolk index of the Alabio duck egg.